Pola Pengembangan Paragraf Pada Majalah Neotech - Julpandi, Julpandi; Gunawan, Kristian; Fauzi, Fikri; Kurniawan, Eva Dwi (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2025)
This research examines paragraph development patterns in the text of the July 2001 edition of Neotech Magazine using qualitative descriptive methods. Data was obtained through documentation studies and note-taking techniques, with a focus on analyzing the structure and linguistic elements of paragraphs. The research results identified five dominant paragraph development patterns: chronology, illustration, definition, comparison, and cause and effect. The chronology pattern is used to show the time sequence in technological development, the illustration pattern provides a concrete picture of technological concepts, the definition pattern explains technical terms, the comparison pattern contrasts various technologies, and the cause-and-effect pattern explains causal relationships in technological development. The use of these patterns helps writers convey technology information effectively to readers, with each pattern having a specific function in increasing reader understanding. This research contributes to the development of more effective technology text writing strategies and can be used as a reference in technology journalistic writing.